Revitalisasi Ruang Ibadah dan Pusat Komunitas Desa Melalui Kegiatan Bersih-Bersih Musholla dan Balai Desa Pasinan Kecamatan Lekok - Amalia Salsabilla; Abdullah Ilmi; Rekha Widiawati; Cilda Thesisa Ilmawan Dzinnur; Nelud Daraajatul Aliyah; Suwito Suwito; Rommy Hardyansah (Institut Teknologi dan Bisnis Semarang, 2024)
Revitalization of the prayer room and community center of Pasinan village, Lekok District, which is carried out routinely every Friday and Sunday involving student participation and collaboration with village communities from various circles. This activity aims to create a clean, comfortable and conducive environment for religious and social activities. And able to improve the quality of life of the community through developing village potential. By creating a clean and healthy environment, it is hoped that it can encourage increased social, economic and cultural activities in the community, so that in the end it will contribute to village progress. Through this activity of cleaning prayer rooms and village halls, we succeeded in cleaning prayer rooms which were initially reluctant to be used again and the environment around the prayer rooms was not good as well as the program for cleaning and tidying up the grounds of the Pasinan village hall which was still not well implemented. Apart from that, this activity also succeeded in strengthening ties between residents and increasing awareness of the importance of keeping the environment clean. Through this activity, it is hoped that collective awareness can be raised regarding the importance of maintaining environmental cleanliness and maintaining public facilities as shared assets. As a follow-up, it is planned to carry out similar activities periodically and involve more parties.